From Feeling Threatened to Conservative Turn: Challanges toward Promoting Moderate Islam through New Media - Yahya Fathur Rozy (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2023)
Abstract : The notion that Islam in Indonesia is â€œIslam with a smiling faceâ€ seems to have started to be reviewed. That nickname was popular in Indonesia in the 1700s to 1800s. However, since the collapse of the New Order (Orde Baru), the face of Islam in Indonesia has rapidly changed. It has turned gloomy and full of anger marked by the growth of discourses of religious conservatism and fundamentalism. This phenomenon is called a â€œconservative turnâ€. All this has resulted in the eroding of moderate Islamic discourse. Two of the largest Islamic organizations in Indonesia, NU and Muhammadiyah, to stem the conservative turn trend, still continue trying to spread the idea of moderate Islam in various ways despite challenges, criticism, and obstacles. Using the feeling threatened theoretical framework and virtual ethnographic method, this research wants to focus on IBTimes.ID's (online media affiliated to Muhammadiyah) efforts to moderate and reconcile conflicts and tensions between Sunnis and Shia in Indonesia. This research seeks to answer questions about: (1) What obstacles did IBTimes.ID experience when conducting a moderate Islam campaign? (2) How can feeling threatened that led to conservative turn become the big challenges for campaign of religious moderation by IBTimes.ID?